Salinity contrast in the US Midcontinent Sea during Pennsylvanian glacio-eustatic highstands: Evidence from conodont apatite δ 18O - Joachimski, Michael; Lambert, Lance; Joachimski, Michael (Palaeogeography, Palaeoclimatology, Palaeoecology, 2015)
Pennsylvanian phosphatic black shales are widely interpreted to have been deposited in waters deep enough to produce a pycnocline that would have developed as a consequence of increased riverine runoff into the largely landlocked North American Midcontinent Sea during the more humid interglacial intervals of the Late Palaeozoic Ice Age. We tested whether a gradient in surface water salinity existed in the North American Midcontinent Sea during times of maximum flooding by analyzing oxygen isotopes of conodont apatite from correlative Pennsylvanian black shales of the Midland, Midcontinent, Illinois and Appalachian basins. In the Midland and Midcontinent basins, average δ18O values for conodonts from the Oakley (middle Desmoinesian/upper Moscovian), Hushpuckney (lower Missourian, lower Kasimovian) and Heebner black shales (lower Virgilian/lower Gzehlian) are 18.8±0.3‰, 19.1±0.2‰, and 18.9±0.1‰, respectively. Oxygen isotope ratios of conodonts from the Nuyaka Creek black shale (uppermost Desmoinesian/upper Moscovian) of the Midcontinent Basin are 19.8±0.3‰, and thus significantly higher in comparison to the other black shales. These higher values support previous interpretations that the Lost Branch is a minor cyclothem, with south polar regions having been less deglaciated than during the interglacial phases of the more widespread major cyclothems. Conodonts from Oakley shale equivalents from Ohio and Pennsylvania are depleted in 18O on average by 2.5‰ in comparison to conodonts from the Midcontinent Basin. This pattern is also evident for conodonts from the Heebner and Hushpuckney shales, although conodonts from the Appalachian Basin show only a 0.4-0.7‰ depletion in 18O compared to conodonts from the Midcontinent Basin. The differences in δ18O are interpreted as reflecting primarily salinity, assuming that temperature was relatively constant across the palaeotropical Midcontinent Sea.Lower salinities in the Appalachian Basin and a significant salinity gradient in the Midcontinent Sea were reconstructed for the Desmoinesian Oakley shale, supporting the idea that freshwater discharge resulted in a salinity-stratified water column during times of "everwet" tropical palaeoclimate, at least in the eastern part of the epeiric sea. However, the salinity gradient is considerably reduced during the subsequent Missourian and Virgilian periodically dry interglacial periods (Hushpuckney and Heebner shales). This suggests that surface waters in the Midcontinent Sea were not significantly influenced by continental runoff and calls into question whether a halocline was necessary for the formation of phosphatic core shales.
Keywords: Conodont; Oxygen isotopes; Pennsylvanian; Salinity; US Midcontinent